2019
DOI: 10.1002/admi.201901393
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Enhancement of Electroactive Biomass/Polypyrrole Hydrogels for High Performance Flexible All‐Solid‐State Supercapacitors

Abstract: Recently, electroactive biomass‐based hydrogels have attracted great attention for flexible supercapacitor electrodes due to its porous, renewable, earth‐abundant, low‐cost, and environmentally friendly characters. However, it is challenging to facilely prepare biomass‐based hydrogels with simultaneously possesses high mechanical strength and excellent electrochemical performance. In this work, the lignosulfonate/polypyrrole (Lig/PPy) hydrogel (LP54) is obtained. In order to further improve the mechanical stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…hibited ah ighe nergyd ensity of 76.7 mWhcm À2 at al ow power density of 2mWcm À2 ,a nd the energy density still remained 42.3 mWhcm À2 at ah igh powerd ensity of 25 mW cm À2 ,w hich correspond to volumetric energy densities (E V )o f1 2a nd 6.6 mW hcm À3 at volumetric powerd ensities (P V ) of 0.31 and 3.9 Wcm À3 ,r espectively.F rom Figure7e, it was observed that the flexible supercapacitorm anufactured with LNF-0.1 electrodes could provideb etter electrochemical performance than those flexible supercapacitors reported previously,s uch as graphene/polypyrrole//graphene/polypyrrole (22.9 mWhcm À2 at 0.56 mW cm À2 ), [20] Ni-Co oxide@MnO 2 //AC (52 mWhcm À2 at 17.3 mW cm À2 ), [21] Cu(OH) 2 /CPCC//AC/CC (49 mWhcm À2 at 0.6 mW cm À2 ), [22] NiO@MnO 2 //Fe 2 O 3 (9.62 mWhcm À2 at 28.9mWcm À2 ), [23] Cu-CAT-NWAs/PPy//Cu-CAT-NWAs/PPy (22.4 mWhcm À2 at 1.1 mW cm À2 ), [24] MoS 2 /MnS/GR// MoS 2 /MnS/GR (7 mWhcm À2 at 49.9 mWcm À2 ), [25] Mn 3 O 4 /Gas// CNHs/Gas (14.7 mWhcm À2 at 14.1 mW cm À2 ), [26] and FPCSLP 54 // FPCSLP 54 (72.5 mWhcm À2 at 250 mWcm À2 ). [27] Moreover,tocompare the performance based on the mass of the electrodes, we calculated the energy density (E m in Whkg À1 )a nd power density (P m in Wkg À1 )o ft he flexible device according to the mass of active material( FigureS10, Supporting Information). The device delivered am aximal energy density of 36.5 Whkg À1 at a power density of 0.95 kW kg À1 ,a nd the energy density still remained 20.2 Whkg À1 at ah igh power density of 11.9 kW kg À1 .…”
Section: Electrochemical Performanceo Fflexible Devicementioning
confidence: 99%
“…hibited ah ighe nergyd ensity of 76.7 mWhcm À2 at al ow power density of 2mWcm À2 ,a nd the energy density still remained 42.3 mWhcm À2 at ah igh powerd ensity of 25 mW cm À2 ,w hich correspond to volumetric energy densities (E V )o f1 2a nd 6.6 mW hcm À3 at volumetric powerd ensities (P V ) of 0.31 and 3.9 Wcm À3 ,r espectively.F rom Figure7e, it was observed that the flexible supercapacitorm anufactured with LNF-0.1 electrodes could provideb etter electrochemical performance than those flexible supercapacitors reported previously,s uch as graphene/polypyrrole//graphene/polypyrrole (22.9 mWhcm À2 at 0.56 mW cm À2 ), [20] Ni-Co oxide@MnO 2 //AC (52 mWhcm À2 at 17.3 mW cm À2 ), [21] Cu(OH) 2 /CPCC//AC/CC (49 mWhcm À2 at 0.6 mW cm À2 ), [22] NiO@MnO 2 //Fe 2 O 3 (9.62 mWhcm À2 at 28.9mWcm À2 ), [23] Cu-CAT-NWAs/PPy//Cu-CAT-NWAs/PPy (22.4 mWhcm À2 at 1.1 mW cm À2 ), [24] MoS 2 /MnS/GR// MoS 2 /MnS/GR (7 mWhcm À2 at 49.9 mWcm À2 ), [25] Mn 3 O 4 /Gas// CNHs/Gas (14.7 mWhcm À2 at 14.1 mW cm À2 ), [26] and FPCSLP 54 // FPCSLP 54 (72.5 mWhcm À2 at 250 mWcm À2 ). [27] Moreover,tocompare the performance based on the mass of the electrodes, we calculated the energy density (E m in Whkg À1 )a nd power density (P m in Wkg À1 )o ft he flexible device according to the mass of active material( FigureS10, Supporting Information). The device delivered am aximal energy density of 36.5 Whkg À1 at a power density of 0.95 kW kg À1 ,a nd the energy density still remained 20.2 Whkg À1 at ah igh power density of 11.9 kW kg À1 .…”
Section: Electrochemical Performanceo Fflexible Devicementioning
confidence: 99%
“…However, the typical low conductivity of resulting structures is a barrier that has been successfully circumvented by the development of composites with conducting polymers due to their high intrinsic conductivity of candidates such as polypyrrole and polyaniline. Despite these superior properties, the low mechanical resistance and low cycle life of CPs-based supercapacitors require a strong interaction of a covering layer with carbon-based systems to reach a desirable energy density in all-solid devices [110].…”
Section: Biomass Carbon Electrodes For Pseudo-capacitance/ Edlc Hybrimentioning
confidence: 99%
“…The dispersion of graphene-based materials is challenging in the preparation of composites. Lignosulfonate, a main by-product in the acidic sulfite pulping process, has aroused wide interest due to its features of low cost and availability as a surfactant resource (Nagaraju et al 2014;Zhao et al 2015;Rębiś and Milczarek 2016;Xiong et al 2016;Peng et al 2019;Wu and Zhong 2019). Li et al (2017) reported a novel metal-free flexible supercapacitor based on lignosulfonate functionalized graphene hydrogels with an impressive specific capacitance of 432 F g -1 in aqueous electrolyte; Xu et al (2020) produced a composite hydrogel supercapacitor electrode material with RGO and graphene quantum dots (GQDS), and the highly porous structure and active sites of GQDS resulted in an excellent electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%